TL, EPR, and optical properties of undoped and Eu-, Ce-, Tb-, Sm-, Cu-, Mn-, and Li- doped MgSiO3 phosphors, synthesized by sol-gel combustion technique - Ccollque-Quispe, A.A.; Giron-Asto, G.; Gonzales-Lorenzo, C.D.; Gundu Rao, T.K.G.; Turpo-Huahuasoncco, K.V.; Aragón, F.F.H.; Villegas-Lelovsky, L.; Watanabe, S.; Ayala-Arenas, J.S. (Elsevier, 2024)
Polycrystalline MgSiO3 samples, undoped or doped with rare earth- (Eu, Tb, Ce, Li, Sm), transition- (Mn and Cu), and alkali metal- (Li) elements, were prepared by the sol-gel combustion method and characterized by thermoluminescence, electron spin resonance, and optical properties. Enstatite and protoenstatite phases are observed in undoped and doped MgSiO3. Better TL results have been observed for phosphors doped with Tb, Ce, and Li (0.5 % mol). Fading experiments and the GCD method have been performed. EPR signals of gamma-irradiated phosphors indicate the formation of radiation-induced defect centers. Cu-doped MgSiO3 shows an unusual feature of the Cu2+ ion. The Cu2+ ion occupies a tetragonally compressed octahedral site, presenting an unconventional attribute. Optical bandgap value Eg is higher for the Ce, Tb, Mn, Li, Sm, and Cu-doped MgSiO3 phosphors. Ce, Li, and Tb dopant ions were found suitable for the MgSiO3 sample regarding its thermoluminescent response and its possible application in radiation dosimetry.
Keywords: Polycrystalline MgSiO3; Sol-gel combustion; Thermoluminescence (TL); Electron Paramagnetic Resonance (EPR); Radiation Dosimetry; Dopant effects; https://purl.org/pe-repo/ocde/ford#1.03.02